THE EFFECTIVENESS OF WORK MOTIVATION AND EMPLOYEE ABILITIES IN REGIONAL GOVERNMENT ORGANIZATIONS IN REGENCY IN THE PROVINCE OF GORONTALO - Syamsu Qamar Badu; Novianty Djafri (Journal of Artificial Intelligence and Digital Economy, 2024)
A government organization has predetermined goals. Success in achieving these goals does not only depend on government operational funds, facilities, infrastructure, and technology, but also on human resources. Therefore, this research aims to examine the influence of work motivation and employee abilities on the effectiveness of local government organizations, with the hypothesis that "there is a positive influence of work motivation and employee abilities on organizational effectiveness." The study employs a causal survey method, incorporating multiple regression analysis techniques. This research employs a quantitative approach, obtaining, processing, and analyzing data statistically (parametrically). This research concludes, based on the carried out data analysis, that: (i) the combination of work motivation and ability significantly influences organizational effectiveness; (ii) work motivation partially influences organizational effectiveness; and (iii) ability partially influences organizational effectiveness.